The Failure of Risk Management : Why It's Broken and How to Fix It. - Hubbard, Douglas W. (John Wiley & Sons, Incorporated, 2020)
"The Failure of Risk Management is about a serious problem in the business of risk analysis and how to fix it. Basic analysis methods are unused, or misapplied, in many major corporate and government decisions. This book shows how some of the most popular "risk analysis" methods are no better than astrology -they are not based on anything an actuary or statistician would recognize as sound, quantitative analysis. Businesses, governments, and the public have completely unrealistic perceptions of risk, currently. This book addresses proper risk methodology, to educate decision makers across industries. This new edition will include new examples citing recent events (e.g. hurricanes and data breaches), new statistical methods, and updated data"--